Is the world heading towards a clash of civilizations in the post 11 Septermber 2001 environment? - Subramaniyan, R. (2008)
Samuel Huntington wrote that the fundamental source of conflict in this new world will not be primarily ideological or economic but will be predominantly cultural. It is argued in this paper that culture matters and it is an important factor but apart from culture, economics and power or the lack of it is the more fundamental source of conflict.